2021
DOI: 10.3390/microorganisms9071445
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Monosaccharides by Hungateiclostridium thermocellum ATCC 27405 through Adaptive Evolution

Abstract: Hungateiclostridium thermocellum ATCC 27405 is a promising bacterium for consolidated bioprocessing with a robust ability to degrade lignocellulosic biomass through a multienzyme cellulosomal complex. The bacterium uses the released cellodextrins, glucose polymers of different lengths, as its primary carbon source and energy. In contrast, the bacterium exhibits poor growth on monosaccharides such as fructose and glucose. This phenomenon raises many important questions concerning its glycolytic pathways and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(172 reference statements)
1
1
0
Order By: Relevance
“…Contrary to previous reports ( 17 ), transporter A in C. thermocellum was confirmed to be the sole glucose transporter in our study, instead of transporter C. This finding is indeed consistent with those of two recent studies involving the adaptive evolution of C. thermocellum on glucose and fructose, which showed that transporter A genes contained the most frequent mutations in the adaptive strains ( 21 , 22 ). Unlike other monosaccharide-binding proteins with strong affinities to the substrate ( K D in the μM range) ( 51 ), the binding of CbpA to glucose is remarkably weak as shown by ITC experiments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Contrary to previous reports ( 17 ), transporter A in C. thermocellum was confirmed to be the sole glucose transporter in our study, instead of transporter C. This finding is indeed consistent with those of two recent studies involving the adaptive evolution of C. thermocellum on glucose and fructose, which showed that transporter A genes contained the most frequent mutations in the adaptive strains ( 21 , 22 ). Unlike other monosaccharide-binding proteins with strong affinities to the substrate ( K D in the μM range) ( 51 ), the binding of CbpA to glucose is remarkably weak as shown by ITC experiments.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are quite unexpected, because many microorganisms are known to have a multiplicity of redundant sugar transporters for their major carbon source ( 51 , 52 ). C. thermocellum takes up cellodextrins derived from cellulose as its major carbon source, while monosaccharides, such as glucose and fructose, can also be utilized by the bacterium after a lengthy adaptation period ( 21 , 22 ). Although the physiological and evolutionary benefits of these restrictive transporters are still unknown, these findings suggest that engineering sugar transporters in C. thermocellum could be easier than in species with multiple redundant transporters.…”
Section: Discussionmentioning
confidence: 99%